Expression profiling of various genes during the fruit development and ripening of mango - Pandit, Sagar S.; Kulkarni, Ram S.; Giri, Ashok P.; Koellner, Tobias G.; Degenhardt, Joerg; Gershenzon, Jonathan; Gupta, Vidya S. (Plant Physiology and Biochemistry, 2010)
Mango (Mangifera indica L. cv. Alphonso) development and ripening are the programmed processes; conventional indices and volatile markers help to determine agronomically important stages of fruit life (fruit-setting, harvesting maturity and ripening climacteric). However, more and precise markers are required to understand this programming; apparently, fruit's transcriptome can be a good source of such markers. Therefore, we isolated 18 genes related to the physiology and biochemistry of the fruit and profiled their expression in developing and ripening fruits, flowers and leaves of mango using relative quantitation PCR. In most of the tissues, genes related to primary metabolism, abiotic stress, ethylene response and protein turnover showed high expression as compared to that of the genes related to flavor production. Metallothionin and/or ethylene-response transcription factor showed highest level of transcript abundance in all the tissues. Expressions of mono- and sesquiterpene synthases and 14-3-3 lowered during ripening; whereas, that of lipoxygenase, ethylene-response factor and ubiquitin-protein ligase increased during ripening. Based on these expression profiles, flower showed better positive correlation with developing and ripening fruits than leaf. Most of the genes showed their least expression on the second day of harvest, suggesting that harvesting signals significantly affect the fruit metabolism. Important stages in the fruit life were clearly indicated by the significant changes in the expression levels of various genes. These indications complemented those from the previous analyses of fruit development, ripening and volatile emission, revealing the harmony between physiological, biochemical and molecular activities of the fruit. (C) 2010 Elsevier Masson SAS. All rights reserved.
Keywords: Mangifera indica; Stress response; Terpene metabolism; Transcriptome analysis